Assessing multidisciplinary follow-up pattern efficiency and cost in follow-up care for patients in cervical spondylosis surgery: a non-randomized controlled study - Fu, Zhongmin; Xie, Yan; Li, Peifang; Gao, Menghui; Chen, Jiali; Ning, Ning (Frontiers in Medicine, 2024)
Background: The use of multidisciplinary treatment programs in out-of-hospital healthcare is a new area of research. Little is known about the benefits of this method in the management of discharged patients undergoing cervical spondylosis surgery.Objective: This study aimed to explore the effect of a contracted-based, multidisciplinary follow-up plan in patients after cervical spondylosis surgery.Methods: This non-blinded non-randomized controlled study was conducted with 88 patients (44 in the intervention group, 44 in the control group). The clinical outcomes, including Neck Disability Index (NDI), pain score (VAS), Self-Efficacy for Managing Chronic Disease 6-item Scale (SECD-6), and 12-Item Short-Form Health Survey (SF-12) score were assessed at the time of discharge, 24-72 hours, 1 month, and 3 months post-discharge. The complications, patient satisfaction, and economic indicators were assessed at the final follow-up (3 months).Results: Patients who received contracted follow-up showed greater improvement in neck dysfunction at 24-72 hours, 1 month, and 3 months after discharge compared to those who received routine follow-up (P < 0.001). At 1 month after discharge, the intervention group exhibited better self-efficacy (P = 0.001) and quality of life (P < 0.001) than the control group, and these improvements lasted for 3 months. The intervention group reported lower pain scores at 24-72 hours and 1 month (P = 0.008; P = 0.026) compared to the control group. The incidence of complications was significantly lower in the intervention group (11.4%) compared to the control group (40.9%). The total satisfaction score was significant difference between the two groups (P < 0.001). Additionally, the intervention group had lower direct medical costs (P < 0.001), direct non-medical costs (P = 0.035), and total costs (P = 0.04) compared to the control group. However, there was no statistically significant difference in indirect costs between the two groups (P = 0.59).A multidisciplinary contract follow-up plan has significant advantages regarding neck disability, self-efficacy, quality of life, postoperative complications, patient satisfaction, and direct costs compared with routine follow-up.